PADDY CUM PRAWN FARMING (POKKALI FIELDS) OF KERALA - C. Sudhan; H.S. Mogalekar; K. Ranjithkumar and Patadiya Dhaval Sureshbhai (INTERNATIONAL JOURNAL FOR INNOVATIVE RESEARCH IN MULTIDISCIPLINARY FIELD, 2016)
The Pokkali field are unique ecosystem of central Kerala with rich biodiversity and capacity to generate organic salt resistant paddy cum shrimp/fish. Salt tolerant strain of paddy cultivated in coastal areas for six months from May to October followed by Filtered shrimp or Prawn or fishes culture during November to April under traditional farming system of about 12,986.6 ha in Kerala. Rice cultivation alone not profitable under the organic farming, but the overall Pokkali farming system is made highly profitable by including prawn cultivation in the succeeding season. Around six species of shrimps, three species of prawns, three species of crabs and over 23 species of fishes have been recorded from the Pokkali field of Kerala. Paddy yield from traditional practices ranges from 1.0 to 1.5 tonnes per ha and that of high yielding varieties ranges from 3.2 to 3.5 tonnes per ha.